A snap-shot assessment of carbon emission and export in a pristine river draining permafrost peatlands (Taz River, Western Siberia) - Vorobyev, Sergey N.; Pokrovsky, Oleg S.; Korets, Mikhail; Shirokova, Liudmila S. (Frontiers in Environmental Science, 2022)
Mobilization of dissolved organic carbon (DOC) and CO2 from the frozen peat to surface waters in the permafrost zone is expected to enhance under on-going permafrost thaw and active layer thickness deepening in high latitude regions. The rivers draining permafrost peatlands of large continental planes are most sensitive to climate warming and may turn out to be very important sources of dissolved carbon to the ocean and CO2 emission to the atmosphere, strongly underestimated at the present time. Here we explored one of the most remote, pristine, unregulated and yet environmentally important western Siberian river (Taz). In a snapshot study during summer baseflow (July 2019), we monitored day time CO2 and CH4 concentrations and measured CO2 emissions using floating chambers in the main stem (700 km from the upper reaches to the mouth) and 17 main tributaries and we assessed day/night variations in the emissions. We further tested the impact of various landscape and lithological parameters of the watershed and tributaries. We revealed sizable emission from the main stem and tributaries (1.0±0.4 and 1.8±0.6 g C-CO2 m-2 d-1, respectively). The CO2 concentrations positively correlated with dissolved organic carbon (DOC), whereas the CH4 concentrations positively correlated with dissolved nutrients (N, P) and proportion of light coniferous forest at the watershed. The overall C emission from the water surfaces (4,845 km²) of the Taz basin (150,000 km²) during open water period (6 months, May to October) was estimated as 0.92 Tg C (> 99.8% C-CO2, < 0.2% C-CH4) which is twice higher than the total dissolved C (organic and inorganic) export flux during the same period). Applying a substituting space for time approach for northern and southern parts of the river basin, we suggest that the current riverine CO2 emission may increase 2 to 3 fold in the next decades due to on-going climate warming and permafrost thaw.